2021
DOI: 10.1002/elsa.202100003
|View full text |Cite
|
Sign up to set email alerts
|

A binder‐free composite of graphite and kaolinite as a stable working electrode for general electrochemical applications

Abstract: Composite electrodes are essential to overcome dynamic challenges related to electrodes made of polymeric binders. Herein, this work reports a composite electrode consisting of graphite and kaolinite (GKCE) as a potential alternative for commercial electrodes. The GKCE series exhibits exponential decay in resistivity parallel to the linear increase in mechanical strength depending on the relative strength of the unique lamella‐like graphite structure when going from low to high graphite percentage. GKCE with 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Mechanical compression is used to fabricate TKMCP, resulting in a highly compressed clay matrix embedded with TiO2 particles (Figure 8). The authors of the current study previously reported the formation of tiny clay particles during the fabrication of graphite-clay composite electrodes using a similar technique [27][28][29] . However, even with the same fabrication technique, the outcomes of the current study are significantly different, resulting in clay sheets rather than tiny particles.…”
Section: Resultsmentioning
confidence: 93%
“…Mechanical compression is used to fabricate TKMCP, resulting in a highly compressed clay matrix embedded with TiO2 particles (Figure 8). The authors of the current study previously reported the formation of tiny clay particles during the fabrication of graphite-clay composite electrodes using a similar technique [27][28][29] . However, even with the same fabrication technique, the outcomes of the current study are significantly different, resulting in clay sheets rather than tiny particles.…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, having a readily available photocatalyst that can be easily synthesized on a large scale is more important. The authors of the present study recently developed a novel composite preparation method based on mechanical compression and heat treatment, resulting in a stable binder-free graphite and clay composite electrode [21][22][23][24][25]. Following a similar technique, authors recently developed efficient binary photocatalysts that are composed of raw materials, including TiO2 and clay (kaolinite/MMT), resulting in improved photocatalytic activity and mechanical strength [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical activity of these synthesized electrodes has been explored and established. [34][35][36] This work reports the electrochemical sensing of Hb on graphitekaolin clay composite (GK) modified SPCE (GK/SPCE) in an alkaline medium. The sensing was based on the one-step conversion of Hb to alkaline hematin without using any toxic reagents, followed z E-mail: tg_satheesh@cb.amrita.edu; pv_suneesh@cb.amrita.edu by its electrooxidation on the modified electrode.…”
mentioning
confidence: 99%